Journalism Education in Turkey in the Spiral of Neoliberal Policies and Technological Transformation: Problems, Pursuits, and Suggestions - Mehmet GUZEL; Meltem GONDEN (Anı Publishing, 2022)
In recent years, radical changes in journalism due to political developments and technological innovations have accelerated the debate on the quality and future of journalism education. Today, as in the rest of the world, journalism academics in Turkey are faced with the need to restructure journalism education in line with the transformation of journalism and the problems as well as needs that come with it. Considering the structural problems of the media sector in Turkey and the need for quality journalism, the role of journalism academics in this process becomes even more important. On the other hand, in Turkey, where journalism education is a field with multifaceted problems because of neoliberal policies, how communication faculties and journalism departments can respond to the current needs of journalism education constitutes a critical issue. Based on these evaluations, this study focuses on the current needs and the pursuits for future journalism education of journalism academics in Turkey and their experiences under current conditions. With a qualitative research approach, interviews were conducted with seven faculty members of different backgrounds working in journalism departments affiliated to public and foundation universities in Turkey. According to the results, journalism academics had practices to structure training programs in line with the developments and needs in journalism and there were inequalities in this regard, especially in newly established departments. It was also revealed that the ongoing problems arising from higher education policies in journalism education generally complicate the efforts of journalism academics to respond to current needs.